Greece : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics, Banking Supervision, Insurance Supervision, Securities Regulation, and Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses key findings of the Financial System Stability Assessment on Banking Supervision, Insurance Supervison, Securities Regulation, and Anti-Money Laundering and Combating the Financing of Terrorism for Greece. The Greek financial sector appears largely sound and resilient to potential adverse shocks. The banking system is well capitalized and profitable, with adequate liquidity, but faces challenges arising from the recent rapid credit growth that increases bank exposure to unfamiliar credit risks. Strategic and medium-term challenges include addressing legal and institutional impediments to improving competitiveness and developing new, cost-efficient sources of funding.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet